A Review of Breeding Systems in the Pineapple Family (Bromeliaceae, Poales) - Cascante Marín, Alfredo (2023)
Breeding systems play an essential role in plant sexual reproduction and influence speciation and extinction processes. However, our understanding of the breeding systems for particular neotropical angiosperm families is inadequate. The Pineapple family (Bromeliaceae) is one of the few indigenous and highly diverse plant lineages native to the American Continent and is a resource for the ornamental plant industry. Bromeliads have a remarkable history of adaptive radiation, yet the role of breeding systems in their evolution and ecology is still unknown. This review aims to establish the current state of knowledge on breeding systems in Bromeliaceae by identifying general patterns, data limitations, and information gaps. We compiled data on self-compatibility (SC), autonomous self-fertilization (selfing), and apomixis based on a thorough review of the scientific literature from 1990 to 2020. The final database included 177 entries, which represented 26 genera and 152 species (4.1% of the family). Two-thirds of the studies were conducted on species from highly diverse genera: Aechmea, Pitcairnia, Tillandsia, and Vriesea. Bromeliaceae exhibit a wide variety of breeding systems (SC and selfing). Subfamilies Pitcairnioideae (sensu stricto) and Tillandsioideae had higher values of SC and selfing, although some of the most investigated genera in each subfamily exhibited contradictory patterns and data for subfamilies considered ancestral were absent. Complete apomixis was rare, but it was more prevalent in Pitcairnioideae. The evolution of autofertility is likely the combined result of floral herkogamy as well as the species’ self-compatibility. Our present understanding of the evolutionary advantages of selfing in Bromeliaceae is limited and deserves further investigation.